Chicken Management Systems and Egg Production in Delta State Nigeria``````````````````` - Ovwigho, B.O.; Bratte, L.; Isikwenu, J.O. (International Journal of Poultry Science, 2008)
````The study was necessitated by the need to stir the minds of chicken egg producers towards adopting the best chicken management system. The extensive system of rearing chicken for egg is old and still remained the most popular in the study area. Commercial eggs production was carried out on a large scale by the few farmers who practiced the intensive (battery cage) chicken management system. A significant (p < 0.05) and high degree of positive relationship (r = 0.70) was found between chicken management system and level of egg production. Majority of the farmers would require general education, fund and technical training in poultry production to enable them adopt the intensive (battery cage) management system of rearing chickens for egg production. Mostly local chickens were reared under the extensive system. No matter the popularity, the extensive system of rearing chickens lacks the potential for increased egg production. Egg protein is regarded as luxury to the extent that children who consume eggs are regarded as thieves among most of the poor in Nigeria. More poultry farmers need to embrace the intensive (battery cage) system in order to meet the egg protein needs of the people of Delta State, Nigeria.